Feasibility study of enhancing DNA isolation using rapid prototyped magnetic beads premixer - Ong, Teddy Eng Hoo. (2008)
[THIS THESIS CONSISTS OF TWO (2) PARTS - THIS IS PART 1]. In molecular biology, separation and sampling techniques of biological cells, enzymes, antigens, or DNA are very important to detect and analyze small amount of bio-molecules. In biotechnology, magnetic separation is a critical technique, superparamagnetic beads in the prder of a few microns have recently been used to help manipulate and to transport bio-molecules. These special beads are essential for separating target bio-molecules or bacteria. Development of micro bio-separators and mixers has been considered as one of the most difficult tasks due to its fluidic and complex interconnections of the microfluidic components. Good micromixer designs are neccessary to achieve high capture or extraction of target bio-molecules from minute sample liquid, which is extremely important for down stream bio-processing. In general, micromixers can be categorized as passive micromixers and active micromixers. This project looks at the design and development of such mixing principles which produced more efficient results and new ideas in mixing knowledge and concepts.